1994
DOI: 10.1007/bf00244025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamic effects during venous air infusion and after decompression in pigs

Abstract: We have compared haemodynamic effects of venous gas emboli during continuous air infusion into the right atrium and after rapid decompression in pigs. Eight anaesthetized and spontaneously breathing pigs received continuous air infusion at a rate of either 0.05 ml.kg-1.min-1 (six pigs, air infusion group) or 0.10 ml.kg-1.min-1 (two pigs). Another eight pigs (decompression group) underwent a 30-min compression to 5 bar (500 kPa, absolute pressure), followed by a rapid decompression (2 bar.min-1). Haemodynamic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…To our knowledge, this is the Wrst study showing a clear FeNO increase following embolization with gas in amounts comparable with that seen in models of decompression sickness (Vik et al 1994). Two prior studies have measured NO in association with gas infusions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To our knowledge, this is the Wrst study showing a clear FeNO increase following embolization with gas in amounts comparable with that seen in models of decompression sickness (Vik et al 1994). Two prior studies have measured NO in association with gas infusions.…”
Section: Discussionmentioning
confidence: 83%
“…See also less than that liberated in decompression sickness. For example, Vik et al (1994) found that a continuous infusion of 50 l kg ¡1 min ¡1 elicited a similar response in pulmonary artery pressure (PAP) as animals underwent a 30-min compression to 5 bar followed by a rapid decompression (2 bar min ¡1 ), although the bubble count was much lower in the decompression group.…”
Section: Discussionmentioning
confidence: 91%
“…As the VGE get trapped however in the pulmonary microcirculation, they provoke a gradual increase in pulmonary artery pressure (PAP). PAP may rise by 15-20% after 20-30 min; this depends on the severity of the pulmonary embolization [36]. As a consequence of this rise in PAP, after a short time also the right atrial pressure will increase, allowing a more frequent or more abundant shunting into the left atrium [37].…”
Section: Vge Pathway Through the Pfomentioning
confidence: 99%
“…Paradoxical arterial embolism may occur, due to intracardiac shunts or transpulmonary passage of the bubbles [15,20]. Subsequent compromise of the coronary blood flow is presumed to be the cause of death, either from intracardiac gas or from pulmonary vascular obstruction leading to reduced blood flow from the right to the left heart [5,21]. In addition to their mechanical effects, gas bubbles can also cause biophysical effects at the bloodbubble interface.…”
Section: Discussionmentioning
confidence: 98%
“…Gases were infused through a 0.062-inch internal diameter femoral venous catheter. Bubble size was not measured since any bubbles which remained undissolved upon reaching the heart would coalesce and then be fractured into bubbles of different sizes by the pumping of the ventricle [21]. Mean pulmonary arterial pressure (MPAP) was used as a clinical measure of the degree of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%